Utilization Pattern of Information and Communication Technologies among the Farming Community of West Bengal (Indian Journal of Extension Education, 2024)
Information and Communication Technologies (ICTs) represent a pivotal paradigm shift, rendering agricultural extension services more realistic and efficient manner, especially in the ever-changing agrarian landscape. Considering the importance of ICTs among rural producers, a study was conducted in the year 2021 to delineate the utilization pattern of ICTs in two purposively selected districts of West Bengal, one representing an agriculturally prosperous district (Purba Burdwan), while other being a backward district (Birbhum), constituting randomly selected 160 respondents engaged in crop and dairy farming. The information about weather forecasting for crop production and dairy animal management was the most utilized information by Purba Burdwan farmers, contrasting to Birbhum farmers’ focus on marketing of crop produce and breeding of animals. Television and smartphones were the most preferred ICT tools. Multiple comparisons by Duncan Multiple Range Test revealed a notable disparity in ICT usage between the districts, with Purba Burdwan farmers exhibiting higher utilization levels. Additionally, the study identified strategic pathways to enhance ICT adoption, especially in the backward districts, thereby offering a roadmap for elevating the socio-economic conditions of farmers in these regions.